All eggs in one basket: A reflection on Malawi’s dependence on agricultural growth strategy - Droppelmann, Klaus; Makuwira, Jonathan; Kumwenda, Ian (International Food Policy Research Institute, 2012)
Recently, there has been a resurgence of interest in the study of structural transformation. However, Africa has received little attention despite the fact that its rural areas seem to be very poor and unproductive relative to urban areas. This case study provides a reflection on challenges faced and development strategies adopted by successive governments in Malawi. Malawi is a country with a complex history of rural-urban transformation. On one hand, Malawi has long been, and still is, a predominantly agrarian economy that has seemingly undergone relatively little rural-urban transformation. Malawi is still predominantly rural, most migration is rural-to-rural, and its economic base is heavily dominated by the production of maize (largely for domestic consumption) and tobacco (largely for exports). In this paper we analyze the macroeconomic policy situation and document patterns and trends in Malawi‘s rural-urban transformation in a systematic manner. To that end, we focus on a number of dimensions of this transformation, including urban population growth, migration patterns, employment trends, and a spatial analysis of agglomerations and connectivity to major urban centers. We then turn to explain these patterns, largely in terms of colonial, post-independence, and more recent history of agricultural policies. We also examine migration patterns (both rural-urban and rural-rural), and constraints on the development of the nonfarm sector. In conclusion it becomes apparent that Malawi must diversify its economy to sustain poverty reduction and economic growth. However, it is not clear whether Malawi has an obvious comparative advantage in any sizeable nonfarm sector and how exactly the economic diversification process is to be achieved.